Effectiveness of Iron and Giving Tablets Folic Acid and Hemoglobin Content on the Improvement of Student Learning Outcomes - Rahmawati, Eli (International Journal of Psychosocial Rehabilitation, 2020)
One of the problems faced by Indonesian teenagers are micronutrient nutrition, which is about 12% of boys and 23% of adolescent girls are anemic, mostly due to iron deficiency. Anemia in adolescents adversely affect the decline in immunity, concentration, academic achievement, teen fitness and productivity. In addition, specifically anemia experienced by young women a more serious effect, considering they are the mothers who become pregnant and give birth to a baby, thus increasing the risk of maternal mortality, premature birth and low birth weight (LBW). The provision of iron tablets along with other micronutrients (multiple micronutrients) is more effective in improving iron status, compared to only provide iron supplementation in the form of a single dose. Objective is known effectiveness of iron and acid tablets to Increased levels of hemoglobin and Student Learning Outcomes. Design this study is a Quasi Experimenta pre and post test without control. Place of research in Prodi D-III Midwifery Balikpapan with the number of sample of 33 female students. Analyze data usingPaire frequency distribution and sample t test. Measuring instrument research were: 1) a questionnaire (the characteristics of respondents, age, history of malaria, Final menstrUji pattern Semesteri) Examination Antopometri to measure: IMT 3) laboratory tests measure the levels of worm infestation and HB. The mean value of the variable posttest hemoglobin levels higher than the average pretest. The mean value of the variable learning outcomes posttest lower than the mean value of the pretest.The provision of iron and folic acid tablets are not effective against the increase in Hemoglobin and Outcomes Study on the students level II Prodi D-III Midwifery Balikpapan.